Toll-like receptor stimulation induces higher TNF-alpha secretion in peripheral blood mononuclear cells from patients with hyper IgE syndrome (2008)
ABSTRACT: Hyper IgE syndromes (HIES) are primary immunodeficiency disorders of unknown pathogenesis. Patients are typically affected with 'cold' abscesses of the skin, recurrent cyst-forming pneumonia, chronic mucocutaneous candidiasis and other less frequent features such as progressive skeletal abnormalities. Defective signaling in the Toll-like receptor (TLR) pathways has been suggested as a responsible pathologic mechanism, however, in previous reports, 10 patients revealed no defect in inflammatory cytokine responses to different TLR ligands. Here, we report the increase in pro-inflammatory cytokines TNF-alpha and IL-8, following TLR2 and TLR4 stimulation in a larger cohort of 25 additional patients with HIES, and provide a meta-analysis of the TLR data in HIES.